Human Rights and Views of the Catholic Church under Habermas Discourse Theory - Madung, Otto Gusti Ndegong; Sihombing, Adison Adrianus; Prasojo, Zaenuddin Hudi (Journal of Southeast Asian Human Rights, 2023)
This article aims to explain the views of the Catholic Church on human rights and put them into dialogue with the concept of human rights based on discourse theory as put forward by Jürgen Habermas. In the view of the Catholic Church, the ethical basis for the concept of human rights is the biblical view of human beings as being made in the image of God, which later became the forerunner to the birth of the concept of human dignity and the ethical basis for human rights. This article shows that the discourse theory rejects this theological model of justification for human rights. The criticism of the discourse theory as it relates to an absolute paradigm is that the absolute paradigm requires metaphysical premises. However, in a modern society characterized by a pluralism of worldviews and philosophical and religious beliefs, such metaphysical claims are no longer acceptable. Through the lens of discourse theory, the foundation of the notion of human rights cannot be based on the pre-political basis of religious values. This discourse theory grounding model is based on the conditions of contemporary post-metaphysical society, characterized by a plurality of comprehensive doctrines. However, Habermas emphasizes the role of religion in the public sphere in promoting human rights. He advocates for the reinvention of public reason by encouraging religious people to translate sacred terms into secular language when entering formal political spaces. According to Habermas’ theories, democratic decision-making must allow citizens the right to use religious terms in public debate. Furthermore, this article shows that discourse theory creates a roadmap for human rights by allowing religion, law, and politics to coexist. Only if we adhere to the principles of discourse theory can we guarantee the fair and just participation of both secular and religious members in a democratic constitutional state. Keywords: Human Rights, Catholic Church, Religion, Habermas’s Discourse Theory